Menghidupkan Budaya Literasi di Lingkungan Sekolah SDS Al-Amien Pamekasan - Devie Reztia Anjarani; Fetty Nuritasari; Anisa Fajriana Oktasari; Yuliarsih Yuliarsih; Rohmah Indahwati (Gapenas Publisher, 2022)
The Community Service (PkM) activity carried out by the Madura University PKM team with the theme